The Experience of Primiparous Mothers in Regulating Emotions during the Postpartum Period - Naiva Urfi Layyinah; Zainal Abidin (Kuras Institute, 2023)
Right after giving birth, a mother is faced with various roles and responsibilities while also undergoing the process of recovery. These experiences often bring out negative emotions, particularly for first-time mothers. If these negative emotions are not managed properly, they can worsen their conditions. This study aimed to gain an overview of the experience of regulating emotions during the postpartum period for primiparous mothers. The study used a qualitative approach through a case study method. In-depth interviews were conducted with three participants, who had given birth to their first child within the past six months, to gather data. The results of the data analysis, using thematic analysis, revealed four themes: Strategies for handling situations, strategies to shift attention, strategies for cognitive change, and strategies to change responses. The mothers reported feeling better after using strategies that allowed them to modify situations, appraise them positively, and express emotions rather than avoiding or suppressing them. The results of this study enhance our understanding of the experience of emotion regulation in primiparous mothers. Hence, mothers can benefit from these strategies for regulating emotions. Partners, parents, and counseling professionals around the mothers can encourage the use of these strategies to process negative emotions effectively.